2020
DOI: 10.3390/medicina56100552
|View full text |Cite
|
Sign up to set email alerts
|

Local Vibrational Therapy for Essential Tremor Reduction: A Clinical Study

Abstract: Background and objectives: tremor is an unintentional and rhythmic movement of any part of the body that is a typical symptom of Essential Tremor (ET). ET impairs the quality of life of patients and is treated with pharmacotherapy. We investigated the tremor reduction efficacy of an innovative vibrational medical device (IMD) in ET patients. Materials and Methods: we conducted a prospective, single-center, single-arm, pragmatic study in ET patients with an extended safety study to evaluate the efficacy and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…terapia se pueden observar hasta cuatros horas de mejoría en el temblor 68 . Sin embargo, el efecto de la estimulación vibratoria sobre el temblor no ha demostrado un efecto consistente de reducción de la intensidad de temblor en pacientes con TE 69 .…”
Section: Consideraciones Metodológicas De La Estimulación Eléctricaunclassified
See 1 more Smart Citation
“…terapia se pueden observar hasta cuatros horas de mejoría en el temblor 68 . Sin embargo, el efecto de la estimulación vibratoria sobre el temblor no ha demostrado un efecto consistente de reducción de la intensidad de temblor en pacientes con TE 69 .…”
Section: Consideraciones Metodológicas De La Estimulación Eléctricaunclassified
“…Sin embargo, el efecto de la estimulación vibratoria sobre el temblor no ha demostrado un efecto consistente de reducción de la intensidad de temblor en pacientes con TE 69 . La escasez de estudios de eficacia de estos dos dispositivos y otros abordajes similares 67,68,70,71 , sumada a la ausencia de reducción de temblor descrita 69 , generan controversia sobre sus beneficios reales en temblor. Además, se desconocen estudios de eficacia de los movimientos giroscópicos sobre el temblor, por lo que se requieren futuros estudios que corroboren el efecto beneficioso de estos dispositivos.…”
Section: Consideraciones Metodológicas De La Estimulación Eléctricaunclassified
“…However, cooling or warming the limb had no effect on tremors in the upper limb [28]. In addition, vibration therapy has been tested on ET and PD patients, and devices like the Vilim ball (various frequencies from 8 to 18 Hz and 0-2 mm amplitude) work based on vibration therapy [30]. It was further indicated that mechanical vibration with a frequency between 50 and 450 Hz could not reduce hand tremors for ET [31].…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Generally, classifying tremor levels based on frequency falls within the range of 4 to 18 Hz [1]. Tremors can be classified according to whether they happen at rest, the action, or with a particular posture of a patient [4]. Essential and Parkinson's tremors are the most common types in the world [5].…”
Section: Introductionmentioning
confidence: 99%